Extended projection, a new method to extract efficient programs from constructive proofs - Takayama, Yukihide (Shin-Sedai-Konpyūta-Gijutsu-Kaihatsu-Kikō <Tōkyō>: ICOT technical report, 1989)
Abstract: "This paper gives a method to extract redundancy free programs from constructive proofs, using the realizability interpretation. The proof trees are analyzed in the style of program analysis, and they are mechanically translated into trees with additional information, called marked proof trees. The program extractor takes marked proof trees as input, and generates programs in a type-free lambda calculus with sequences."